Innovative Activities of Public Sector Enterprises in the Context of Poland’s Economic Growth in 2012–2021 - Brożek, Katarzyna (Journal of Public Governance, 2023)
Objectives: The principal aim of the paper is to analyse and assess the impact of the innovative activities of public sector enterprises on the change in GDP per capita in Poland. The object of the research turned out to be public sector enterprises, but the analysis was extended to include NUTS2 units. Therefore, 16 Polish Provinces were examined in this respect. The research period covered the years 2012–2021. Research Design & Methodology: In the theoretical part, a critical analysis of the literature on the subject was used, while in the empirical part, statistical analysis was provided. The empirical analysis included the characterisation of the selected features, an analysis of basic descriptive statistics, and an analysis of the obtained results. The collected data was prepared using descriptive statistics – mean values, median, minimum and maximum values, first and third quartiles, and distance from the average value, as well as changes in relation to the base year. Several predictors were identified and determined in an arbitrary manner, allowing research to be conducted and conclusions to be drawn. Pearson correlation analysis was also used, the results of which made it possible to determine the strength of the relationship between the examined measures in the field of innovative activitiesof public sector enterprises and Poland’s economic growth. Findings: The main conclusions at the national level include, firstly, that in the analysed period in the Polish economy, on average 26% of public sector enterprises were innovative industrial entities.Secondly, the most frequently introduced type of innovation in the surveyed sector were new or improved processes; the average percentage of enterprises generating this type of activity was 24%. Thirdly, on average, 19.4% of public sector enterprises incurred expenditure on innovation activities, but in 2021, this percentage increased by slightly over 3 percentage points.However, at the regional level, the following regularities can be formulated. Firstly, both in terms of the highest average percentage of innovative industrial enterprises and the highest average expenditure on innovative activities, the Silesian Province was the leader, followed closely by the Masovian Province. A completely different situation concerned the regions for which the percentages of these predictors turned out to be the lowest, i.e. the Lubusz Province and the Warmian-Masurian Province. Secondly, the average share of net revenues from the sale of innovative products in total net revenues from sales in three Provinces, i.e. Pomeranian, Sub-Carpathian, and Łódź, turned out to be higher than the average share for Poland. Implications/Recommendations: The practical implication of the study may be the identification of several predictors of innovative activity of the public sector that influences Poland’s economic growth (measured by the growth dynamics of GDP per capita); the obtained results provide some scope for applying a targeted policy aimed at developing the innovativeness of public sector enterprises in Poland on the one hand, and at improving the attractiveness and competitiveness of the economy on the international arena on the other. Contribution/Value Added: The practical implication of the study may be the identification of several predictors of innovative activity of the public sector that influences Poland’s economic growth (measured by the growth dynamics of GDP per capita); the obtained results provide some scope for applying a targeted policy aimed at developing the innovativeness of public sector enterprises in Poland on the one hand, and at improving the attractiveness and competitiveness of the economy on the international arena on the other.